Corrosion mechanism in PVD deposited nano-scale titanium nitride thin film with intercalated titanium for protecting the surface of silicon. (20th February 2018) - Chaudhry, A.U.; Mansoor, Bilal; Mungole, Tarang; Ayoub, Georges; Field, David P.
Abstract: In this work, thin film systems consisting of: (i) monolithic titanium nitride, (ii) monolithic titanium, and, (iii) titanium nitride with intercalated titanium, were fabricated on <100> P-type Si wafers by magnetron sputtering. The thin films were characterized using electron microscopy, glancing angle x-ray diffraction and nanoindentation. Their impedance response was studied via open circuit potential and electrochemical impedance spectroscopy in a sodium chloride aqueous solution. The influence of intercalated Ti thickness on impedance behavior was investigated in detail. Scanning electron microscopy analysis confirmed the columnar structure of TiN and aggregated structure of Ti thin films. Further microstructural analysis confirmed the presence of nano-porosities in thin films which explained their low modulus and hardness. Analysis of impedance data with equivalent circuit models indicated that incorporation of titanium as intercalated layer between titanium nitride and silicon surface, greatly altered the impedance characteristics of Si. Higher impedance values of thin films were achieved for bi-layer configuration at a much smaller total thickness as compared to monolithic counterparts. The increase in impedance was attributed to the presence of less defective and compact intercalated Ti layer that effectively interrupted the corrosive ions pathways.